Performance Planning in Determining the Direction of Organizational Work Orientation - Makmur Syukri; Syafaruddin Syafaruddin; Novita Sari (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study discusses the planning of teacher performance in determining the direction of organizational work orientation at MTS Al-Washliyah beach pumpkin what activities must be carried out to achieve organizational goals; the research method uses a qualitative descriptive approach, the results of this study are based on the results of research observed from a conclusion regarding the planning and implementation of performance in determining the direction in the organization at MTS Al-Washliyah Pantai Labu, namely by implementing the Teacher's performance plan will provide a successful orientation at MTS Al-Washliyah Pantai Labu. In organizational performance planning, performance planning aims to provide information about what must be carried out on each individual in the corporate environment. The result is that performance planning is the process of compiling a plan as the implementation or elaboration of the program that has been determined in a strategic plan.